2017
DOI: 10.1007/s13592-017-0543-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the own colony odor on olfactory and thermal preferences of the honeybee (Apis mellifera) workers

Abstract: -Honeybee foragers were tested on their preference for the own colony odor either separately, in an olfactometer, or in combination with their temperature preference, in thermal gradient chambers, where their motor activity was also recorded. The bees in the gradient chambers were either deprived of their colony odor for 9 days or exposed to the odor during the experimental days 4-9. The source of odor was wax from the own colony. Bees were attracted by the odor, and this attraction culminated at night. Therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In the studies, we recorded a tendency to reverse the circadian rhythm of thermal preference of the queenless groups of bees containing no more than 20 members in comparison to that of single bees separated from their sisters. The isolated bees selected significantly higher ambient temperature during the day than those at night, which was confirmed in our subsequent studies [37,38]. In another investigation (unpublished data), we examined the effect of group size and found the tendency to reverse the day-night shifts in selected ambient temperature at the size exceeding seven worker bees in queenless groups.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In the studies, we recorded a tendency to reverse the circadian rhythm of thermal preference of the queenless groups of bees containing no more than 20 members in comparison to that of single bees separated from their sisters. The isolated bees selected significantly higher ambient temperature during the day than those at night, which was confirmed in our subsequent studies [37,38]. In another investigation (unpublished data), we examined the effect of group size and found the tendency to reverse the day-night shifts in selected ambient temperature at the size exceeding seven worker bees in queenless groups.…”
Section: Discussionsupporting
confidence: 70%
“…This suggests that the queen’s presence might promote a sleep-like state in bees at nighttime. In our previous investigation [ 38 ], we showed that the own colony odor, emitted by fresh beeswax pieces placed in the gradient chambers, also calmed isolated bee workers, but the effect was not so strong and the odor did not modify the daily pattern of the bees’ thermal preference, i.e., they kept on selecting higher ambient temperatures during the day than those at night. Such a pattern, which is typical for single worker bees separated from their sisters, represents a heterothermic strategy of nocturnal saving energy necessary for morning warm-up under outdoor conditions [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation